1975
DOI: 10.1111/j.1365-2842.1975.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of the occlusion—aetiology, symptomatology and treatment

Abstract: Aetiological factors which lead to occlusal collapse have been surveyed and the clinical symptomatology of this syndrome emphasized. The sequence of periodontal treatment as well as suggestions for re-establishing and recording new jaw relations are discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 4 publications
0
11
0
5
Order By: Relevance
“…This condition is considered to be a risk factor for occlusal instability, as extensive and uncontrolled migration of the teeth might occur leading to collapse of the bite (mandibular overclosure) and further breakdown of the dentition (Ramfjord & Ash, 1983;Mohl et al, 1988; Thomson, 1990). This occlusal collapse is also described by Stern & Brayer (1975) as they stated: 'Pathological changes of the occlusion may occur when posterior tooth support is reduced or lost'. Pointing to the aetiology they noted: 'One of the commonest causes of occlusal collapse is the unreplaced loss of the lower first molar.…”
Section: Introductionmentioning
confidence: 88%
“…This condition is considered to be a risk factor for occlusal instability, as extensive and uncontrolled migration of the teeth might occur leading to collapse of the bite (mandibular overclosure) and further breakdown of the dentition (Ramfjord & Ash, 1983;Mohl et al, 1988; Thomson, 1990). This occlusal collapse is also described by Stern & Brayer (1975) as they stated: 'Pathological changes of the occlusion may occur when posterior tooth support is reduced or lost'. Pointing to the aetiology they noted: 'One of the commonest causes of occlusal collapse is the unreplaced loss of the lower first molar.…”
Section: Introductionmentioning
confidence: 88%
“…It is thought that posterior support prevents or reduces manifestations of the so-called posterior bite collapse. This collapse is accompanied by migrations in the premolar regions, interdental spacing, decrease in vertical dimension, changes in temporomandibular condyle position, overeruption of unopposed teeth, and increased vertical overlap and flaring of anterior teeth [7]. Previous studies showed that in moderate shortened dental arches these phenomenons are just limited or even absent.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, the evidence for this association is still controversial. For example, Kozawa et al 25 demonstrated that mandibles and condyles easily displaced after taking off posterior occlusal contacts forming the supporting zone of the mandible.…”
Section: -11mentioning
confidence: 99%